Indo-Pasifik dalam perspektif geopolitik dan geostrategi - Rodon Pedrason (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
Indo-Pacific cannot be interpreted as a form of integration based on a region or regional areas such as Asia, or Southeast Asia, and Europe, which is based on the geographical shape of the region. The Indo-Pacific emerged as part of a geopolitical and geostrategic study based on competition patterns and state perspectives and behavior based on a broader scope of maritime interests. Indo-Pacific analysis as an object from a geopolitical and geostrategic perspective does not refer to national or regional coverage but to the global area and level. Therefore, the Indo-Pacific analysis used document analysis. In document analysis, this study combines the analysis of three primary data and 50 secondary data from national journals and international journals. In this analysis more directed at the strategic meaning of each country towards the Indo-Pacific strategic value which is then related to the maritime interests of each actor. This study describes the struggles of interests in the framework of competition through geopolitical policies and geostrategy, especially by countries that have influence. Global or the ability to shape political and security structures in the Indo-Pacific.